Nickel oxide-embedded tapered fibre as a saturable absorber for ultrafast photonics - Mahdi, Mohd Adzir; Che Aziz, Siti Asma; Mohd Yusoff, Norita; Zainol Abidin, Nadiah Husseini; Che Abdullah, Che Azurahanim; Idris, Muhammad Idzdihar; Alresheedi, Mohammed Thamer; Ng, Eng Khoon (Elsevier GmbH, 2023)
This work demonstrates a femtosecond pulse generation of erbium-doped fibre laser utilising nickel oxide (NiO) as saturable absorbing material. The prepared composite of NiO/polydimethylsiloxane (PDMS) was successfully transferred onto a plane of tapered fibre through spin- coating technique. Based on the evanescent field interaction of NiO at tapered fiber region, the fabricated NiO/PDMS-saturable absorber exhibited 4.0% modulation depth and 135.5 MW/cm 2 saturation intensity. The integration of this saturable absorber device established a mode-locked operation at 50.0 mW pump power, with ultrafast pulse width of 793 fs operating at the centre wavelength of 1561.27 nm. The pulse repetition rate of 8.0 MHz, with 0.89 nJ energy was attained at 250.0 mW pump power. These research findings open an avenue for further advancement of transition metal oxides in the future of ultrafast photonics.